Marketing Mix of Malaysia Passenger Car Tyre and the Paradigm Shift towards Relationship Marketing in the Contemporary Market - Ong, Li Yun (2010)
In Malaysia, tyre manufacturers have minimal control over the retail business operations because most of the tyre retailers are typically owned by individual owners. Such business environment has restraint tyre manufacturers to continue focusing on traditional marketing mix elements in marketing its products in the past decades. Various literatures have shown that traditional marketing mix must be adapted to incorporate the unique aspects of services. Due to the highly direct customer interactions, relationship marketing which emphasis on enhancing customer relationships has become an essential area for tyre manufacturers and retailers to increase perceive value and create individual competitive advantage.